Peran Guru Pendidikan Agama Kristen sebagai Teladan dalam Pencegahan Bullying Peserta Didik di SMA Negeri 2 Siborong-Borong - Ganda Uli Simarangkir (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
This study aims to examine the role of Christian religious education teachers as role models in preventing bullying in the environment of SMA Negeri 2 Siborong-Borong. Bullying in schools is a serious problem that can hurt student's mental and emotional development. As respected figures and role models, teachers have a key role in creating a safe and respectful environment. In this study, the author highlights various ways in which teachers can play an active role, such as being an example of positive behaviour, building good relationships with students, teaching the values ​​of empathy and tolerance, and enforcing anti-bullying rules firmly. The method used in this study is a qualitative approach by presenting descriptions of literature, books and journals that are linked to the context of teachers and students at SMA Negeri 2 Siborong-Borong. The results of the study indicate that the role of teachers as role models is very important in creating a school culture that is free from bullying and increasing students' awareness of the dangers of bullying and the importance of mutual respect. Thus, the role of teachers as role models in preventing bullying can significantly impact creating a safe and comfortable learning atmosphere for all students.